Dinamika Interaksi Manusia, Masyarakat, dan Budaya dalam Era Globalisasi dan Modernisasi - Harniati Hapsah, Romlah; Az Zahrah, Fatimah; Yasin, Muhammad (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
Humans are social creatures, humans always live in groups to interact and communicate because of their desire to connect with other people and blend in with the surrounding environment. This research focuses on what is the role of humans in forming and maintaining society and culture? and how globalization and modernization affect the relationships between people, society, and culture. This research has two objectives, namely to explain the role of humans in forming and maintaining society and culture and to explain how globalization and modernization affect the relationship between humans, society and culture.  The method in this research uses qualitative methods with observation and interview techniques. The results of this research show that the role of humans in maintaining and forming society and culture is very complex and broad. Starting from forming the values ​​and norms that exist in society so that it becomes a culture that must be maintained and developed in the future. Then the influence of globalization and modernization on human relations, society and culture is very significant.  However, with the positive and negative impacts of the development of globalization and modernization each bringing advantages and disadvantages to human life, therefore, we as humans must be able to balance and sort the two well.